Managing Non-Sewered Human Waste Using Thermochemical Waste Treatment Technologies: A Review - Farhad Beik (MDPI AG, 2021)
The utilisation of micro-scale thermal treatment technologies for non-sewered applications has been emerging as a prominent route for the safe treatment and disposal of high water content hazardous feedstock. This study provides a comprehensive review of the technological concepts practiced up to date in commercial/pilot and small scales for various types of solid fuels. The respective challenges are critically described and discussed to aid in the selection of promising technology for on-site sanitary applications. Furthermore, the challenges observed with the nominated (pyrolysis) technology are discussed in detail and addressed. This study suggests rapid energy recovery from by-products primarily made up of the highest yield of syngas with a desirable calorific value. The optimum operating ranges are discussed to ensure a reliable thermal conversion of sludge materials considering the application constraints and technology drawbacks. However, further studies are needed to investigate the uncertainties regarding emissions, energy consumption and overall associated costs.